2006
DOI: 10.1002/lt.20907
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychiatric complications after adult living donor liver transplantation

Abstract: We investigated the psychosocial effects of a right hepatectomy on donors for adult living donor liver transplantation (ALDLT). Questionnaires were sent to 66 actual donors, who had undergone ALDLT between August 1998 and September 2003, as well as to 139 potential donors, who had been examined as possible candidates for ALDLT; the latter had been excluded and had not undergone surgery. All actual donors reported full recovery within an average period of 14.41 (standard deviation ϭ 8.86) weeks; all had returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 17 publications
9
85
2
3
Order By: Relevance
“…The current literature provides several studies examining HRQoL in liver donors, in which the number of patients ranged between 22 and 127. 13,14,[33][34][35][36][37][38][39][40][41] The SF-36 is the most frequently used tool for measurement of HRQoL, and the scores are comparable to the findings in our present study. [34][35][36][37]40,41 Compared with the HRQoL shown in the general population, liver donors had equal scores in most examinations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current literature provides several studies examining HRQoL in liver donors, in which the number of patients ranged between 22 and 127. 13,14,[33][34][35][36][37][38][39][40][41] The SF-36 is the most frequently used tool for measurement of HRQoL, and the scores are comparable to the findings in our present study. [34][35][36][37]40,41 Compared with the HRQoL shown in the general population, liver donors had equal scores in most examinations.…”
Section: Discussionsupporting
confidence: 89%
“…[10][11][12][13] Parameters such as the graft type (left or right lobe), donor age, the urgency of the recipient's need for transplant, postoperative and other donor complications, and posttransplant recipient morbidity and mortality were also identified as possible important negative predictive parameters for a poor HRQoL in donors. [14][15][16] However, most studies have been limited by their small sample size, a retrospective single-center study design, and a lack of a standardized assessment of donor HRQoL parameters. Therefore, we performed this study to evaluate both the postoperative morbidity and the short-and long-term influences of LDLT on the HRQoL of donors, as assessed by the established standardized Short Form 36 (SF-36) outcome measurement tool.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Erim et al (15), 6 (14%) living donors -all female -had transient, but severe psychiatric disturbance as depressive disorders in 5 and posttraumatic stress disorder in 1. They suggested that female donors and donors with a more complicated postoperative course more often develop psychiatric symptoms and should receive adequate care (15). Our study seems to support the latter studies displaying negative psychosocial outcomes after LRLT.…”
Section: Discussionmentioning
confidence: 95%
“…However, negative psychosocial outcomes such as clinical depression and somatization have been reported after LRLT in a number of studies (13,14). In the study by Erim et al (15), 6 (14%) living donors -all female -had transient, but severe psychiatric disturbance as depressive disorders in 5 and posttraumatic stress disorder in 1. They suggested that female donors and donors with a more complicated postoperative course more often develop psychiatric symptoms and should receive adequate care (15).…”
Section: Discussionmentioning
confidence: 99%
“…The last is to be considered the most important difference because complications in the recipients were found to have a negative impact on donors' QOL. [3][4][5] However, in another study, 6 no significant differences were observed between donors whose recipients suffered from complications and donors whose recipients did not. As for the donor group, a study comparing right lobe donors with left lobe donors did not find any QOL differences.…”
mentioning
confidence: 84%